Renal Sympathetic Denervation for the Treatment of Difficult-to-Control or Resistant Hypertension - Vasilios Papademetriou; Michalis Doumas; Konstantinos Tsioufis (International Journal of Hypertension)
Hypertension represents a major health problem with an appalling annual toll. Despite the plethora of antihypertensive drugs, hypertension remains resistant in a considerable number of patients, thus creating the need for alternative strategies, including interventional approaches. Recently, catheter-based renal sympathetic denervation has been shown to be fairly safe and effective in patients with resistant hypertension. Pathophysiology of kidney function, interaction and crosstalk between the kidney and the brain, justifies the use of renal sympathetic denervation in the treatment of hypertension. Data from older studies have shown that sympathectomy has effectively lowered blood pressure and prolonged life expectancy of hypertensive patients, but at considerable cost. Renal sympathetic denervation is devoid of the adverse effects of surgical sympathectomy, due to its localized nature, is minimally invasive, and provides short procedural and recovery times. This paper outlines the pathophysiological background for renal sympathetic denervation, describes the past and the present of this interventional approach, and considers several future potential applications.